The Study of Persuasive Strategies from the Messages on Election Campaign Billboards of the Candidates for the 2019 Election of Member of the House of Representativesin Constituency 1, ChanthaburiProvience - Yuttanapongkitti, Patchareeporn; Junwichien, Sutthida; Wareeket, Kanokwan (RBRU Journal of Humanities and Social Sciences (online), 2020)
The objective of this research was to study of persuasive strategies found in messages displayed on election campaign billboards of the candidates for the 2019 election of members of the House of Representatives in constituency 1, Mueang District and Laem Sing District, Chanthaburi Province. Data were 55 billboards of the candidates in constituency 1, Chanthaburi Province, 13th February – 20th March 2019. The surveyed texts were transcribed into 79 messages Persuasive strategy concept of Kanokphan Khamwongpin (2001) was applied as an analytical framework. Research results showed that there were eight persuasive strategies used in total six of them which were consistent with corresponded to the employed framework included rewards appeal 50 messages showing 52.63 percent, the party’s campaign 13 messages 13.68 percent, slogan 13 messages showing 13.68 percent, language of solidarity 9 messages showing 9.47 percent, candidate’s profiles 4 messages showing 4.21 percent. and asking for chance 3 messages showing 3.16 percent respectively other two strategies comprised language of comparison 2 messages showing 2.11 percent, and using a questions 1 messages showing 1.05 percent. The most popular persuasive strategy was reword appeal.